1988
DOI: 10.1101/gad.2.7.901
|View full text |Cite
|
Sign up to set email alerts
|

The proboscipedia locus of the Antennapedia complex: a molecular and genetic analysis.

Abstract: The homeotic proboscipedia (pb) locus of the Antennapedia Complex (ANT-C) directs the differentiation of adult labial and maxillary structures. Loss-of-function pb alleles show a transformation of adult mouth parts to legs and affect maxillary palp morphology. We have identified the pb transcription unit by inducing and analyzing a series of pb null chromosomal breakpoints. In addition, we describe a variegating pb phenotype associated with two rearrangement breakpoints. Having identified the pb locus, we desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(83 citation statements)
references
References 75 publications
3
80
0
Order By: Relevance
“…A similar proposal has been made to explain the brain defects that occur in buttonhead (btd) mutants, although btd is not expressed in NBs of the corresponding brain regions (Younossi-Hartenstein et al, 1997). Molecular characterization of brain neuroblasts Expression of the homeotic gene labial completely covers the anlage of the tritocerebrum We analysed the expression of the homeotic genes proboscipedia (pb) and labial (lab), both members of the ANT-C and known to be expressed in the head ectoderm and in the brain after mid-embryogenesis (Hirth et al, 1998;Pultz et al, 1988). Antibody staining against Pb reveals that at stage 11, the protein is restricted to internal cells of the mandibular segment (presumably mesodermal cells) and to dorsal ectoderm of the maxillary and labial appendages (Pultz et al, 1988) (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…A similar proposal has been made to explain the brain defects that occur in buttonhead (btd) mutants, although btd is not expressed in NBs of the corresponding brain regions (Younossi-Hartenstein et al, 1997). Molecular characterization of brain neuroblasts Expression of the homeotic gene labial completely covers the anlage of the tritocerebrum We analysed the expression of the homeotic genes proboscipedia (pb) and labial (lab), both members of the ANT-C and known to be expressed in the head ectoderm and in the brain after mid-embryogenesis (Hirth et al, 1998;Pultz et al, 1988). Antibody staining against Pb reveals that at stage 11, the protein is restricted to internal cells of the mandibular segment (presumably mesodermal cells) and to dorsal ectoderm of the maxillary and labial appendages (Pultz et al, 1988) (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…The A class Hox Pb is detected in the gnathal segments but has no known function during embryogenesis (Pultz et al, 1988) and has no effect on the expression of optix (not shown).…”
Section: Research Articlementioning
confidence: 99%
“…The following strains were used: (Casanova et al, 1987;Hazelrigg and Kaufman, 1983;Lewis, 1978;Merrill et al, 1989;Pultz et al, 1988;Riley et al, 1987;Struhl, 1983;Wakimoto and Kaufman, 1981), tsh 2757R8 (Laugier et al, 2005) (Rauskolb et al, 1995), hth P2 (Rieckhof et al, 1997), Df(2R)en and wg CX4 (FlyBase Consortium, 1999). prdGal4,UASAntp,UASUbx,, UAS-optix (Seimiya and Gehring, 2000) and UAS-tsh (Manfroid et al, 2004).…”
Section: Drosophila Strainsmentioning
confidence: 99%
“…15). In Drosophila, zen controls all aspects of amnioserosa development; a second copy of zen (z2) is expressed in an identical pattern but is dispensable (16,17). The cells of Zendeficient Drosophila embryos either die or acquire an embryonic fate.…”
mentioning
confidence: 99%